Postemergence herbicides and application time affect wheat yields - Jack P. Orr; Mick Canevari; Lee Jackson; Ray Wennig; Ryan Carner; Gail Nishimoto (California Agriculture, 1996)
Experiments conducted on wheat grown in the Sacramento and San Joaquin valleys found that two of the most critical factors in reducing plant injury are choice of postemergence herbicide and the growth stage at which the herbicide is applied. To minimize risk of wheat injury and to maximize yields, the optima! time to apply postemergence herbicides is at the tillering growth stage. The two-leaf stage is most sensitive to 2,4-D. Moderate or severe injury caused by 2,4-D and dicamba + MCPA on one-third to one-half of spikes can cause yield losses of up to 27%.